Biodegradable mulching film with pest control effect and method of manufacturing thereof
Patent Information
- Application Number
- KR1020240108306
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2044-08-13
Smart Images

Figure 112024088136882-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a biodegradable mulching film having a pest control effect and a method for manufacturing the same. More specifically, the invention relates to a biodegradable mulching film having excellent biodegradability and a pest control effect capable of effectively preventing pests, and a method for manufacturing the same, by pressurizing and compressing a raw material comprising a biodegradable polymer composition and zeolite powder using a molding machine to produce a mulching film. Background Technology
[0002] Generally, mulching film is a vinyl sheet used to cover the surface of cultivated soil during crop cultivation. Its purpose is to increase crop yields by preventing soil erosion, maintaining soil moisture, regulating soil temperature, suppressing weeds, preventing soil-borne pathogens, and preventing soil contamination. Mulching film is manufactured to be black in color to inhibit the germination and growth of weed seeds.
[0003] These agricultural mulching films are manufactured from materials such as polyethylene and polyvinyl chloride, which do not decompose naturally and thus act as a cause of environmental pollution. While agricultural mulching films are essential for efficient cultivation, they must be removed after a certain period. However, due to labor shortages in aging rural societies, these films are often left untreated and abandoned, which is cited as a cause of environmental pollution.
[0004] Therefore, research is currently underway to develop mulching films that can naturally decompose without the need for separate removal and have a significant pest control effect. Prior art literature
[0005] Republic of Korea Published Patent Application No. 10-2024-0065942 (Date of publication: May 14, 2024) The problem to be solved
[0006] The objective of the present invention is to provide a biodegradable mulching film having excellent biodegradability and a pest control effect capable of effectively preventing pests and diseases, and a method for manufacturing the same, by manufacturing a mulching film by pressurizing and compressing a raw material comprising a biodegradable polymer composition and zeolite powder using a molding machine. means of solving the problem
[0007] A method for manufacturing a biodegradable mulching film having a pest control effect according to an embodiment of the present invention for solving the above problem comprises the steps of: feeding a raw material containing a biodegradable polymer composition and zeolite powder into the extrusion part of a molding machine, and then moving it to the die side of the molding machine using the extrusion part of the molding machine to apply pressure; supplying gas to the pressurized material that has passed through the die mounted on the extrusion part of the molding machine to form it; and compressing the molded material to form a biodegradable mulching film; wherein the biodegradable polymer composition comprises 20 to 40 weight% of polybutylene adipate terephthalate; 10 to 30 weight% of polyethylene adipate oligomer; and the remainder being polylactic acid.
[0008] The above gas is air, and the above gas is supplied through an air gun.
[0009] The above compression is carried out at 90 to 130°C under pressure conditions of 100 to 1,000 kgf / ㎠.
[0010] The above biodegradable polymer composition is added in an amount of 300 to 500 parts by weight per 100 parts by weight of the zeolite powder.
[0011] The above biodegradable polymer composition further comprises one or more of 0.5 to 2.0 weight% of an antimicrobial agent, 1 to 3 weight% of a flame retardant, and 1 to 5 weight% of a strength reinforcing agent.
[0012] The above antimicrobial agent is used in a mixture of 40 to 70 weight% lactic acid, 15 to 30 weight% sorbic acid, and 15 to 30 weight% anhydrous citric acid.
[0013] The strength reinforcing agent comprises a first strength reinforcing agent having a first average diameter of 50 to 1,500 nm and a second strength reinforcing agent having a second average diameter of 2,000 to 7,000 nm, which is larger than the first average diameter, and the first strength reinforcing agent is added in an amount of 300 to 500 parts by weight per 100 parts by weight of the second strength reinforcing agent. Effects of the invention
[0014] The biodegradable mulching film having a pest control effect according to the present invention and the method for manufacturing the same are manufactured by pressurizing and compressing raw materials containing a biodegradable polymer composition and zeolite powder using a molding machine to produce a mulching film, thereby enabling effective prevention of pests while maintaining excellent biodegradability.
[0015] As a result, the biodegradable mulching film having a pest control effect according to the present invention and the method for manufacturing the same can be naturally decomposed by being made of a biodegradable material, and can secure a tensile strength of 50 to 60 MPa, thereby having excellent mechanical properties as well as excellent flame retardancy. Brief explanation of the drawing
[0016] FIG. 1 is a process flowchart showing a method for manufacturing a biodegradable mulching film having a pest control effect according to an embodiment of the present invention. Figure 2 is a schematic diagram illustrating a molding machine. Specific details for implementing the invention
[0017] Hereinafter, preferred embodiments of the present invention and the physical properties of each component are described in detail. This description is intended to be sufficient for a person skilled in the art to easily practice the invention, and does not imply that the technical scope and concept of the present invention are limited thereby.
[0018] Hereinafter, a biodegradable mulching film having a pest control effect and a method for manufacturing the same according to a preferred embodiment of the present invention will be described with reference to the attached drawings.
[0019] FIG. 1 is a process flowchart showing a method for manufacturing a biodegradable mulching film having a pest control effect according to an embodiment of the present invention, and FIG. 2 is a schematic diagram for explaining a molding machine.
[0020] As shown in FIGS. 1 and 2, a method for manufacturing a biodegradable mulching film having a pest control effect according to an embodiment of the present invention includes a pressurizing step (S110), a molding step (S120), and a compression step (S130).
[0021] pressurization stage
[0022] In the pressurization step (S110), the raw material (10) containing the biodegradable polymer composition and zeolite powder is fed into the extrusion part (120) of the molding machine (100), and then the extrusion part (120) of the molding machine (100) is used to move it toward the die (130) of the molding machine (100) and pressurize it.
[0023] Here, the molding machine (100) includes an input section (110), an extrusion section (120), a die (130), a supply section (140), a compression section (150), and a winding section (160). At this time, the die (130) may include a body and a through hole formed along a ring shape in the body. The extrusion section (120) may be a screw extruder positioned at the tip of the die (130), and the input section (110) of the molding machine (100) may be provided at the tip of the extrusion section (120).
[0024] The front end and rear end are based on the direction of movement of the raw material (10), the molded product (20) described later, the mulching film (30), etc. in the molding machine (100), and the raw material (10), the molded product (20), and the mulching film (30) can be moved from the front end to the rear end.
[0025] Here, the input section (110) may be a hopper, and the hopper may have an inlet located at the top for introducing raw materials (10) including a biodegradable polymer composition and zeolite powder, and an outlet located at the bottom that communicates with the extrusion section (120).
[0026] In this step, the raw material (10), comprising a biodegradable polymer composition and zeolite powder introduced through the input section (110), is moved to the die (130) by the extrusion section (120). As the screw of the screw extruder rotates, the raw material (10) can be moved toward the die (130) along the threads of the screw.
[0027] Plastic surgery stage
[0028] In the molding step (S120), gas is supplied to the pressurized material that has passed through the die (130) mounted on the extrusion part (120) of the molding machine (100) to form it.
[0029] In this step, gas supply can be performed by the supply unit (140) of the molding machine (100). At this time, the gas may be air, and the supply unit (13) may use an air gun. Through the air gun, a constant flow rate of gas can be sprayed onto the pressurized material.
[0030] The supply unit (140) can be positioned to penetrate the body of the die (130) and the like to discharge gas into the inside of the pressurized material, and the discharge port can be positioned to supply gas into the inside of the pressurized material. In this way, as air, which is gas, is continuously supplied to the pressurized material through an air gun, the pressurized material can be stretched into a bubble shape. The pressurized material can be moved to the side of the compression unit (150) of the molding machine (100), which is positioned above the die (130), by the compression unit (150) and winding unit (160) described later, and can be stretched by the supply unit (140).
[0031] Compression stage
[0032] In the compression step (S130), the molded product (20) is compressed to form a biodegradable mulching film (30).
[0033] Compression can be performed by a compression unit (150) positioned on the upper side of the die (130). The compression unit (150) may include a pair of compression rollers, and the spacing between the pair of compression rollers is positioned to be smaller than the width of the bubble-shaped molded product (20), so that the pair of compression rollers rotate in opposite directions to compress and move the molded product (20) to the rear end, thereby manufacturing the molded product (20) into a biodegradable mulching film (30).
[0034] In this step, it is preferable to perform the compression at 90 to 130°C under pressure conditions of 100 to 1,000 kgf / ㎠, and more preferable to perform it at 100 to 110°C under pressure conditions of 500 to 800 kgf / ㎠.
[0035] If the compression temperature is less than 90℃ or the compression pressure is less than 100kgf / ㎠, it may be difficult to secure sufficient strength. In addition, if the compression temperature exceeds 130℃ or the compression pressure exceeds 1,000kgf / ㎠, it is undesirable because there is a risk that the biodegradable mulching film will tear due to the application of excessive pressure.
[0036] Here, the biodegradable mulching film (30) passing through the compression section (150) can be wound onto the winding section (160) through the winding section (160) which is positioned at the rear end of the compression section (150).
[0037] The biodegradable mulching film manufactured by the above-described method uses a biodegradable polymer composition and zeolite powder as raw materials. In this case, by using a biodegradable polymer composition that is biodegradable and has good moldability as a raw material, it is possible to manufacture a molded product and a biodegradable mulching film using a molding machine.
[0038] Here, the zeolite powder exhibits excellent antibacterial and deodorizing performance and emits far-infrared rays that inhibit the growth of mold or bacteria. As such, by mixing the zeolite powder, which emits far-infrared rays inhibiting the growth of mold or bacteria, with a biodegradable polymer composition and then molding and compressing it to manufacture a biodegradable mulching film, the growth of mold or bacteria is inhibited, thereby effectively protecting crops and providing excellent control effects against pests and diseases.
[0039] It is preferable to use a first zeolite powder having a first average diameter of 10 to 100 nm and a second zeolite powder having a second average diameter of 1 to 10 μm, which is larger than the first average diameter.
[0040] At this time, it is preferable to use a mixture of 10 to 30 weight percent of first zeolite powder and 70 to 90 weight percent of second zeolite powder. This is to maximize far-infrared radiation emissivity by expanding the specific surface area, by adding a large amount of second zeolite powder with a relatively large average diameter and a small amount of first zeolite powder with a relatively small average diameter, thereby dispersing a large amount of large-sized zeolite powder.
[0041] The biodegradable polymer composition comprises 20 to 40 weight% of polybutylene adipate terephthalate; 10 to 30 weight% of polyethylene adipate oligomer; and the remainder being polylactic acid.
[0042] Polybutylene adipate terephthalate (PBAT) may be manufactured by commonly used or known methods, or a commercially available product may be purchased and used. The acid value of polybutylene adipate terephthalate is preferably 0.8 to 1.1 mg KOH / g, and more preferably 0.9 to 1.01 mg KOH / g. When the acid value of polybutylene adipate terephthalate satisfies the above range, the tensile strength and tear strength of the biodegradable high-wem* composition are further improved, and the biodegradation rate can be effectively controlled, which is desirable.
[0043] The weight-average molecular weight (Mw) of polybutylene adipate terephthalate is 100,000 to 300,000 g / mol, and the melting temperature (Tm) can be 90 to 140℃.
[0044] It is preferable that such polybutylene adipate terephthalate be added in an amount of 20 to 40 weight percent based on the total weight of the biodegradable polymer composition, and more preferable that it be added in an amount of 25 to 35 weight percent. When the amount of polybutylene adipate terephthalate added satisfies the above range, a biodegradable mulching film having improved mechanical properties and controllable biodegradation rate can be manufactured.
[0045] Polyethylene adipate (PEA) oligomers may be manufactured by commonly used or known methods, or commercially available products may be purchased and used.
[0046] The weight-average molecular weight (Mw) of the polyethylene adipate oligomer is preferably 3,000 to 4,000 g / mol, and more preferably 3,400 to 3,600 g / mol. When the weight-average molecular weight (Mw) of the polyethylene adipate oligomer satisfies the above range, compatibility with polybutylene adipate terephthalate (PBAT) can be improved, thereby enabling the production of a biodegradable mulching film having improved tensile strength and elongation.
[0047] It is preferable that the polyethylene adipate oligomer be added in an amount of 10 to 30 weight percent based on the total weight of the biodegradable polymer composition, and more preferable that it be added in an amount of 20 to 25 weight percent. When the amount of polyethylene adipate oligomer added satisfies the above range, a biodegradable mulching film having improved mechanical properties and controllable biodegradation rate can be manufactured.
[0048] Polylactic acid (PLA) is one of various biodegradable resins. It is extensively studied in materials engineering, either in its pure form or with the addition of substances harmless to the human body. Its applications are also very broad, such as being used as a carrier in tissue engineering. However, it is a biodegradable resin that possesses several characteristics from a general-purpose commercial perspective, rather than being limited to specialized fields like medicine.
[0049] These polylactic acids have excellent mechanical strength and high thermal stability compared to other biodegradable materials. It is preferable to use polylactic acids with a weight-average molecular weight (Mw) of 10,000 to 250,000. If the weight-average molecular weight of the polylactic acid resin is less than 10,000, it cannot have sufficient heat resistance, and if it exceeds 250,000, it may be difficult to secure mechanical strength.
[0050] It is preferable to add this biodegradable polymer composition in an amount of 300 to 500 parts by weight per 100 parts by weight of zeolite powder. If the biodegradable polymer composition is added in an amount of less than 300 parts by weight per 100 parts by weight of zeolite powder, there is a concern that the moldability and biodegradability will be poor, and if the biodegradable polymer composition is added in an excessive amount exceeding 500 parts by weight per 100 parts by weight of zeolite powder, there is a concern that the relative amount of zeolite powder added will decrease, thereby reducing the effectiveness of controlling pests.
[0051] In addition, the biodegradable polymer composition may further include one or more of 0.5 to 2.0 wt% antimicrobial agent, 1 to 3 wt% flame retardant, 1 to 5 wt% strength reinforcing agent, and 0.5 to 2 wt% 2-phenyl-4-benzyl-5-hydroxymethylimidazole.
[0052] It is preferable to use an antimicrobial agent mixed with 40 to 70 weight% lactic acid, 15 to 30 weight% sorbic acid, and 15 to 30 weight% anhydrous citric acid.
[0053] It is preferable that such antimicrobial agents be added in an amount of 0.5 to 2.0 weight% based on the total weight of the biodegradable polymer composition, and more preferable that they be added in an amount of 1 to 1.5 weight%. If the amount of antimicrobial agent added is too low, less than 0.5 weight%, it is difficult to exhibit antimicrobial and antifungal properties, and if the amount of antimicrobial agent added is too high, exceeding 2.0 weight%, it is uneconomical because the effect does not increase relative to the amount used.
[0054] Flame retardants can generally be flame retardants used in polymer compositions, preferably one or more selected from phosphorus-based flame retardants and polymeric bromine-based flame retardants can be mixed and used, and more preferably, polymeric bromine-based flame retardants are used.
[0055] In the present invention, it is preferable that the flame retardant be added in a content ratio of 1 to 3 weight percent with respect to the total weight of the biodegradable polymer composition, and more preferable that it be added in a content ratio of 1.5 to 2.5 weight percent. If the amount of such flame retardant added is too low, less than 1 weight percent, it is difficult to exhibit flame retardant function, and if it is added in excess of 3 weight percent, it may cause a decrease in mechanical properties.
[0056] Here, specifically, one or more selected from polystyrene bromo flame retardants, polybromoepoxy flame retardants, polybromophenoxy flame retardants, polybromocarbonate flame retardants, and polybromoacrylate flame retardants may be used as polymeric bromine-based flame retardants, and preferably, a polybromoepoxy or polybromophenoxy flame retardant composed of a polymer of brominated bisphenol A diglycidyl ether and brominated bisphenol A is used.
[0057] Strength reinforcing agents are added to reinforce strength and increase specific gravity. It is preferable that the strength reinforcing agent include at least two of talc, barium sulfate, tungsten carbide, alumina, calcium carbonate, magnesium carbonate, and magnesia. Here, it is more preferable that the strength reinforcing agent include a first strength reinforcing agent having a first average diameter of 50 to 1,500 nm and a second strength reinforcing agent having a second average diameter of 2,000 to 7,000 nm, which is larger than the first average diameter.
[0058] Here, it is preferable to add the second strength reinforcing agent in an amount of 300 to 500 parts by weight per 100 parts by weight of the first strength reinforcing agent. The reason for adding a large amount of the second strength reinforcing agent with a relatively large average diameter and a small amount of the first strength reinforcing agent with a relatively small average diameter is that adding a large amount of the second strength reinforcing agent with a large size makes it easier for the small-sized first strength reinforcing agent to fill the space between the large-sized second strength reinforcing agents, thereby greatly improving the filling density and being advantageous for increasing strength and securing high specific gravity.
[0059] It is preferable that the strength reinforcing agent be added in an amount of 1 to 5 weight percent based on the total weight of the biodegradable polymer composition, and more preferable that it be added in an amount of 3 to 4 weight percent. If the amount of such strength reinforcing agent added is too low, less than 1 weight percent, the effects of strength reinforcing and specific gravity increase cannot be properly exerted, and if the amount of strength reinforcing agent added is excessive, exceeding 5 weight percent, there is a high risk that physical properties such as heat resistance will deteriorate.
[0060] 2-phenyl-4-benzyl-5-hydroxymethylimidazole is added to a biodegradable polymer composition and acts as an additive that improves biodegradability without reducing strength.
[0061] It is preferable to add 2-phenyl-4-benzyl-5-hydroxymethylimidazole in an amount of 0.5 to 2 weight% based on the total weight of the biodegradable polymer composition, and more preferable to add it in an amount of 1 to 1.5 weight%. If the amount of 2-phenyl-4-benzyl-5-hydroxymethylimidazole added is less than 0.5 weight%, the effect of improving biodegradability may be insufficient, and if the amount of 2-phenyl-4-benzyl-5-hydroxymethylimidazole added exceeds 3 weight%, the effect of improving biodegradability is negligible and there is a risk of rapidly reducing strength, so this is not desirable.
[0062] It is preferable to use a powder of 2-phenyl-4-benzyl-5-hydroxymethylimidazole having an average diameter of 1 to 5 μm, and more preferable to use a powder having an average diameter of 3 to 4 μm. If the average diameter of 2-phenyl-4-benzyl-5-hydroxymethylimidazole is less than 1 μm, it is not easy to manufacture and may have the disadvantage of significantly reduced moldability, and if the average diameter of 2-phenyl-4-benzyl-5-hydroxymethylimidazole exceeds 5 μm, the strength may decrease.
[0063] The biodegradable mulching film having a pest control effect manufactured by the method according to the embodiment of the present invention described above is manufactured by pressurizing and compressing a raw material containing a biodegradable polymer composition and zeolite powder using a molding machine, thereby having excellent biodegradability and effectively preventing pests.
[0064] As a result, the biodegradable mulching film having a pest control effect manufactured by the method according to the embodiment of the present invention can be naturally decomposed by being made of a biodegradable material, and can secure a tensile strength of 50 to 60 MPa, thereby having excellent mechanical properties as well as excellent flame retardancy.
[0065] Examples
[0066] Hereinafter, the structure and operation of the present invention will be explained in more detail through preferred embodiments of the present invention. However, these are presented as preferred examples of the present invention and should not be interpreted in any way as limiting the present invention.
[0067] Details not listed here can be sufficiently technically inferred by a person skilled in this field, so their explanation will be omitted.
[0068] 1. Manufacture of biodegradable mulching film
[0069] Example 1
[0070] After feeding the raw material containing 500g of a biodegradable polymer composition and 100g of zeolite powder into the extrusion section of the molding machine, it was moved to the die side of the molding machine using the extrusion section of the molding machine and pressurized.
[0071] Next, air was supplied to the pressurized material passing through the die mounted on the extrusion section of the molding machine using a gas gun to form the material.
[0072] Next, a biodegradable mulching film was manufactured by compressing the molded product at a temperature of 110°C under a pressure of 600 kgf / ㎠.
[0073] Here, the biodegradable polymer composition used comprises 32 wt% PBAT, 23 wt% PEA, and the remainder PLA, as described in Table 1, and the zeolite powder used is a first zeolite powder having a first average diameter of 50 nm and a second zeolite powder having a second average diameter of 3 μm, mixed with 20 wt% of the first zeolite powder and 80 wt% of the second zeolite powder.
[0074] Example 2
[0075] As described in Table 1, a biodegradable polymer composition comprising 33 wt% PBAT, 24 wt% PEA, 1 wt% antimicrobial agent, and the remainder PLA was used, and a biodegradable mulching film was prepared in the same manner as in Example 1, except that it was compressed at a temperature of 100°C under a pressure condition of 700 kgf / ㎠.
[0076] Example 3
[0077] As described in Table 1, a biodegradable polymer composition comprising 29 wt% PBAT, 19 wt% PEA, 1.5 wt% flame retardant, and the remainder PLA was used, and a biodegradable mulching film was prepared in the same manner as in Example 1, except that it was compressed at a temperature of 90°C and a pressure of 900 kgf / ㎠.
[0078] Example 4
[0079] As described in Table 1, a biodegradable mulching film was prepared in the same manner as in Example 1, except that a biodegradable polymer composition comprising 27 wt% PBAT, 21 wt% PEA, 1.5 wt% antimicrobial agent, 3.0 wt% strength reinforcing agent, and the remainder PLA was used. Here, the strength reinforcing agent (Al2O3) used was a first strength reinforcing agent having an average diameter of 300 nm and a second strength reinforcing agent having a second average diameter of 4,500 nm, wherein the second strength reinforcing agent was added in an amount of 400 parts by weight per 100 parts by weight of the first strength reinforcing agent.
[0080] Example 5
[0081] As described in Table 1, a biodegradable mulching film was prepared in the same manner as in Example 1, except that a biodegradable polymer composition comprising 25 wt% PBAT, 20 wt% PEA, 1.4 wt% antibacterial agent, 1.3 wt% flame retardant, 2.5 wt% strength reinforcing agent, and the remainder PLA was used. Here, the strength reinforcing agent (Al2O3) used was a first strength reinforcing agent having an average diameter of 400 nm and a second strength reinforcing agent having a second average diameter of 5,000 nm, wherein the second strength reinforcing agent was added in an amount of 450 parts by weight per 100 parts by weight of the first strength reinforcing agent.
[0082] Example 6
[0083] As described in Table 1, a biodegradable mulching film was prepared in the same manner as in Example 1, except that a biodegradable polymer composition comprising 35 wt% PBAT, 22 wt% PEA, 1.6 wt% antibacterial agent, 1.4 wt% flame retardant, 2.7 wt% strength reinforcing agent, and the remainder PLA was used. Here, the strength reinforcing agent (Al2O3) used was a first strength reinforcing agent having an average diameter of 500 nm and a second strength reinforcing agent having a second average diameter of 6,000 nm, wherein the second strength reinforcing agent was added in an amount of 350 parts by weight per 100 parts by weight of the first strength reinforcing agent.
[0084] Example 7
[0085] As described in Table 1, a biodegradable mulching film was prepared in the same manner as in Example 1, except that a biodegradable polymer composition comprising 26 wt% PBAT, 21 wt% PEA, 1.2 wt% antimicrobial agent, 1.5 wt% flame retardant, 2.3 wt% strength reinforcing agent, 1.2 wt% additive, and the remainder being PLA was used. Here, the strength reinforcing agent (Al2O3) used was a first strength reinforcing agent having an average diameter of 300 nm and a second strength reinforcing agent having a second average diameter of 4,500 nm, wherein the second strength reinforcing agent was added at 400 parts by weight per 100 parts by weight of the first strength reinforcing agent. In addition, the additive (2-phenyl-4-benzyl-5-hydroxymethylimidazole) was used as a powder having an average diameter of 3.5 μm.
[0086] Comparative Example 1
[0087] After feeding the raw material containing 500g of a biodegradable polymer composition into the extrusion section of the molding machine, it was moved to the die side of the molding machine using the extrusion section of the molding machine and pressurized.
[0088] Next, air was supplied to the pressurized material passing through the die mounted on the extrusion section of the molding machine using a gas gun to form the material.
[0089] Next, a biodegradable mulching film was manufactured by compressing the molded product at a temperature of 100°C under a pressure condition of 650 kgf / ㎠.
[0090] Here, the biodegradable polymer composition used comprises 50 wt% PBAT and the remainder PLA, as described in Table 1.
[0091] Comparative Example 2
[0092] As described in Table 1, a biodegradable mulching film was prepared in the same manner as Comparative Example 1, except that a biodegradable polymer composition comprising 50 wt% PEA, 1 wt% antimicrobial agent, and the remainder PLA was used.
[0093] Comparative Example 3
[0094] As described in Table 1, a biodegradable mulching film was prepared in the same manner as Comparative Example 1, except that a biodegradable polymer composition comprising 40 wt% PBAT, 40 wt% PEA, 1.5 wt% flame retardant, and the remainder PLA was used.
[0095] (Unit: weight%) division PBAT PEA antibacterial agents flame retardant Strength reinforcing agent additives PLA Example 1 32 23 - - - - Bal. Example 2 33 24 1.0 - - - Bal. Example 3 29 19 - 1.5 - - Bal. Example 4 27 21 1.5 - 3.0 - Bal. Example 5 25 20 1.4 1.3 2.5 - Bal. Example 6 35 22 1.6 1.4 2.7 Bal. Example 7 26 21 1.2 1.5 2.3 1.2 Bal. Comparative Example 1 50 - - - - - Bal. Comparative Example 2 - 50 1.0 - - - Bal. Comparative Example 3 40 40 - 1.5 - - Bal. PBAT: Polybutylene Adipate Terephthalate PEA: Polyethylene Adipate Oligomer PLA: Polylactic Acid Antimicrobial Agent: Lactic Acid 60wt%, Sorbic Acid 20wt%, and Citric Anhydride 20wt% Flame Retardant: Polybromoepoxy Flame Retardant Strength Reinforcer: Alumina (Al2O3) Additive: 2-Phenyl-4-Benzyl-5-Hydroxymethylimidazole
[0096] 2. Evaluation of Mechanical Properties and Biodegradability
[0097] Table 2 shows the mechanical properties and biodegradability evaluation results for the biodegradable mulching films prepared according to Examples 1 to 7 and Comparative Examples 1 to 3. At this time, the biodegradability evaluation was performed by measuring the amount of carbon dioxide generated by the biodegradable mulching films prepared according to Examples 1 to 7 and Comparative Examples 1 to 3 over a period of 180 days under general soil conditions, as per KS M ISO 17556 (measurement of carbon dioxide generation or oxygen consumption), and evaluating it according to the following formula.
[0098] Biodegradability (%) = (Amount of generated carbon dioxide / Amount of theoretical carbon dioxide) x 100
[0099] division Tensile strength (MPa) Growth rate (%) Biodegradability (%) 180 days under general soil conditions Example 1 51 621 87.4 Example 2 52 611 88.1 Example 3 50 617 86.4 Example 4 51 598 87.6 Example 5 53 604 88.3 Example 6 54 603 87.5 Example 7 60 619 89.1 Comparative Example 1 21 651 80.4 Comparative Example 2 19 647 81.7 Comparative Example 3 22 639 81.9
[0100] As shown in Tables 1 and 2, it was confirmed that the biodegradable mulching films prepared according to Examples 1 to 7 exhibited significantly increased tensile strength without a significant decrease in elongation compared to the biodegradable mulching films prepared according to Comparative Examples 1 to 3. In particular, it was confirmed that the biodegradable mulching film prepared according to Example 7 exhibited the highest mechanical properties, showing the highest tensile strength while having a high elongation.
[0101] In addition, it was confirmed that the biodegradable mulching films prepared according to Examples 1 to 7 had a very high biodegradability of 85% or more, while the biodegradable mulching films prepared according to Comparative Examples 1 to 3 had a low biodegradability of 82% or less.
[0102] 3. Antimicrobial Evaluation
[0103] Table 3 shows the results of the antimicrobial evaluation for the biodegradable mulching films prepared according to Examples 1 to 7 and Comparative Examples 1 to 3. For the antimicrobial evaluation, bacterial cells, namely Escherichia coli and Staphylococcus aureus, were inoculated into Lysogeny broth (LB) medium and cultured at 37°C for 8 hours. Subsequently, 1 x 10 4 Up to 1X10 5 2 mL of a bacterial suspension at a concentration of CFU / mL was inoculated into each well of a 6-well plate, and the mulching films of Examples 1 to 7 and Comparative Examples 1 to 3 were cut to a size of 5 cm x 5 cm and placed in each well. The 6-well plates containing the samples were incubated at 37°C for 24 hours, and the number of colonies and bacteria were checked to calculate the removal rate of each bacterium.
[0104] division E. coli removal rate (%) Staphylococcus aureus removal rate (%) Example 1 97.8 97.1 Example 2 99.3 99.2 Example 3 98.6 98.9 Example 4 99.6 99.4 Example 5 99.7 99.8 Example 6 99.7 99.7 Example 7 99.8 99.7 Comparative Example 1 67.5 69.1 Comparative Example 2 70.6 72.3 Comparative Example 3 72.1 71.9
[0105] As shown in Tables 1 and 3, the results of the antimicrobial test on the biodegradable mulching films prepared according to Examples 1 to 7 showed that they exhibited more than 97% antimicrobial activity against Escherichia coli and Staphylococcus aureus after 24 hours.
[0106] On the other hand, the biodegradable mulching films prepared according to Comparative Examples 1 to 3 showed low antibacterial activity of 73% or less against Escherichia coli and Staphylococcus aureus after 24 hours.
[0107] Although the embodiments and comparative examples of the present invention have been described in detail as above, the scope of the present invention is not limited thereto, and the scope of the present invention extends to those that are substantially equivalent to the embodiments of the present invention. Explanation of the symbols
[0108] S110: Pressurization step S120: Forming stage S130: Compression step
Claims
Claim 1 The method comprises the steps of: feeding a raw material containing a biodegradable polymer composition and zeolite powder into the extrusion section of a molding machine, moving it to the die side of the molding machine using the extrusion section of the molding machine, and applying pressure; supplying gas to the pressurized material that has passed through the die mounted on the extrusion section of the molding machine to form it; and compressing the molded material to form a biodegradable mulching film; wherein the compression is performed at 100 to 110°C under pressure conditions of 500 to 800 kgf / ㎠, and the biodegradable polymer composition is added in an amount of 300 to 500 parts by weight per 100 parts by weight of the zeolite powder, and the biodegradable polymer composition comprises 20 to 40 wt% polybutylene adipate terephthalate; 10 to 30 wt% polyethylene adipate oligomer; 0.5 to 2.0 wt% antibacterial agent; 1 to 3 wt% flame retardant; and 1 to 5 wt% strength reinforcing agent. A method for manufacturing a biodegradable mulching film having a pest control effect, characterized by comprising 0.5 to 2 weight% of 2-phenyl-4-benzyl-5-hydroxymethylimidazole and the remainder being polylactic acid, wherein the polylactic acid has a weight-average molecular weight (Mw) of 10,000 to 250,000, and the 2-phenyl-4-benzyl-5-hydroxymethylimidazole is a powder having an average diameter of 1 to 5 μm. Claim 2 A method for manufacturing a biodegradable mulching film having a pest control effect, characterized in that, in claim 1, the gas is air and the gas is supplied through an air gun. Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 A method for manufacturing a biodegradable mulching film having a pest control effect according to claim 1, characterized in that the antimicrobial agent is a mixture of 40 to 70 weight% lactic acid, 15 to 30 weight% sorbic acid, and 15 to 30 weight% anhydrous citric acid. Claim 7 A method for manufacturing a biodegradable mulching film having a pest control effect according to claim 1, wherein the strength reinforcing agent comprises a first strength reinforcing agent having a first average diameter of 50 to 1,500 nm and a second strength reinforcing agent having a second average diameter of 2,000 to 7,000 nm which is larger than the first average diameter, and wherein the second strength reinforcing agent is added in an amount of 300 to 500 parts by weight per 100 parts by weight of the first strength reinforcing agent. Claim 8 A biodegradable mulching film manufactured by a method according to any one of claims 1 to 2 and claims 6 to 7, wherein the biodegradable mulching film has a tensile strength of 50 to 60 MPa and comprises a biodegradable polymer composition and zeolite powder, wherein the biodegradable polymer composition is added in an amount of 300 to 500 parts by weight per 100 parts by weight of the zeolite powder, and the biodegradable polymer composition comprises 20 to 40 wt% polybutylene adipate terephthalate; 10 to 30 wt% polyethylene adipate oligomer; 0.5 to 2.0 wt% antibacterial agent; 1 to 3 wt% flame retardant; and 1 to 5 wt% strength reinforcing agent. A biodegradable mulching film having a pest control effect, characterized by comprising 0.5 to 2 weight% of 2-phenyl-4-benzyl-5-hydroxymethylimidazole and the remainder being polylactic acid, wherein the polylactic acid has a weight-average molecular weight (Mw) of 10,000 to 250,000, and the 2-phenyl-4-benzyl-5-hydroxymethylimidazole is used as a powder having an average diameter of 1 to 5 μm. Claim 9 delete
Citation Information
Patent Citations
Biodegradable Resin Composition and Biodegradable Mulching Film Using of the Same
KR1020140106882A
Biodegradable polymer composition and a biodegradable mulching film comprising the same
KR1020230034467A
Plastic sheet with excellent antibacterial properties and method for manufacturing antibacterial and biodegradable packaging containers by using the same
KR102442491B1
Mulching film manufacturing method
KR102466854B1